Microencapsulated phase change materials with composite titania-polyurea (TiO2-PUA) shell - Zhao, Aiqin (2020)
This paper presents a novel approach to synthesize microencapsulated phase change materials (MEPCMs) with composite titania-polyurea (TiO2-PUA) shell at low temperature. MEPCM pre-microcapsules with PUA shell were first synthesized through interfacial polymerization in oil-in-water emulsion, followed by deposition of TiO2 on the surface of pre-microcapsules in solution by means of the liquid phase deposition (LPD) method at low temperature. The two-step synthesis approach results in high yield of microcapsules and the MEPCMs with composite TiO2-PUA shell integrate advantages of both organic and inorganic shells. Results show that the MEPCMs have a well-defined core–shell structure with around 73 wt.% of core fraction and dense composite TiO2-PUA shell, which is thermally stable and durable and effectively lowers the evaporation and prevents leakage of the core material even under repeated heating and cooling. The MEPCMs also show mitigated supercooling, faster thermal response, and high thermal storage capacity. TiO2-PUA MEPCM-modified cement pastes showed distinct latent heat storage capacity.